Cervical necrotizing fasciitis of odontogenic origin: Case report - Chrcanovic Ramos Bruno; Custódio Neto Luís Antônio (Serbian Medical Society - Dental Section, Belgrade, 2009)
Introduction. Necrotizing fasciitis is a rapidly spreading soft tissue polymicrobial infection characterized by necrosis of the subcutaneous tissue and superficial fascia. When its origin is an odontogenic infection, most cases resulted from an abscessed mandibular molar. The most common significant medical conditions in the patient's history are diabetes, immunodeficiency and substance abuse, between others. Left unchecked this infection invariably leads to systemic toxicity, multi-system organ failure and eventual death. Aggressive and frequent debridement with proper antibiotic and supportive care are essential for limiting morbidity and mortality. Case Report. A case of cervical necrotizing fasciitis involving Streptococcus pyogenes (group A) and Staphylococcus aureus in a 23-year-old woman with history of systemic lupus erythematosus is described. She was taking 20 mg/day prednisolone for 8 months and had a deeply carious tooth. Conclusion. This case shows what tooth decay may cause in immunologically compromised person. The professional should be aware of the early endodontic treatment importance, because when left unchecked, it might lead to an infection of the deep spaces of face and neck, or to cervical necrotizing fasciitis in patients with certain risk factors.